1994
DOI: 10.1161/01.str.25.10.2005
|View full text |Cite
|
Sign up to set email alerts
|

Long-term prognosis of symptomatic lacunar infarcts. A hospital-based study.

Abstract: This study concerns the long-term prognosis of lacunar infarcts. We report the analysis of our hospital-based series of 178 patients consecutively admitted for a lacunar syndrome due to a lacunar infarct diagnosed with computed tomography and magnetic resonance imaging. Demographic data, medical history, vascular risk factors, and imaging data were recorded for each patient. The follow-up was 35 +/- 22 months. The lacunar syndrome was pure motor hemiparesis in 69 patients (39%), ataxic hemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
77
5

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 24 publications
6
77
5
Order By: Relevance
“…In our study hypertension and diabetes were independent predictors for recurrent stroke, in contrast to previous studies in which either no single factor 15,18 or age only 23 was found. The adequacy of risk factor management and compliance to therapy during follow-up was not addressed in our study.…”
Section: Recurrent Strokecontrasting
confidence: 99%
See 3 more Smart Citations
“…In our study hypertension and diabetes were independent predictors for recurrent stroke, in contrast to previous studies in which either no single factor 15,18 or age only 23 was found. The adequacy of risk factor management and compliance to therapy during follow-up was not addressed in our study.…”
Section: Recurrent Strokecontrasting
confidence: 99%
“…Previously reported independent risk factors for death after lacunar infarction are age, diabetes, and smoking (in the study by Clavier et al 15 ) and age and disability score (in the study by Salgado et al 18 ). The high proportion of our patients (54%) not prescribed ASA at discharge from hospital reflects the therapeutic tradition in the mid-1980s, before the wide acceptance of antiplatelet therapy as standard therapy in different thromboembolic disorders.…”
Section: Discussion Survivalmentioning
confidence: 91%
See 2 more Smart Citations
“…A second common principle is that certain stroke comorbidities are strongly associated with poor neurological outcome. In particular, clinical studies have shown that diabetes increases the risk of ischemic stroke and is associated with slower or poorer recovery of function/independence (Clavier et al, 1994;Jorgensen et al, 1994;Hankey et al, 2007;Kamouchi et al, 2011), even when adjusting for confounding factors such as age and stroke severity (Wei et al, 2010).…”
Section: Effect Of Diabetes On Stroke Recoverymentioning
confidence: 99%